The homeodomain transcription factor MEIS1 triggers chemokine expression and is involved in CD8+ T‐lymphocyte infiltration in early stage ovarian cancer. Issue 9 (7th June 2018) - Karapetsas, Athanasios; Tokamani, Maria; Evangelou, Christos; Sandaltzopoulos, Raphael
Abstract : CD8+ T‐lymphocytes infiltration is a favorable prognostic marker in ovarian cancer. Recently we identified MEIS1 as a gene overexpressed in early stage ovarian tumors enriched for CD8+ T‐cells. Here, we report the molecular mechanism of the homeodomain transcription factor MEIS1 in lymphocyte recruitment. We validated that MEIS1 expression is a positive predictor of CD8+ T cells in early stage ovarian cancer. We showed that MEIS1 induces the expression of CCL18, CCL4, CXCL7, CCL5, CXCL1, and IL8 chemokines in cancer cells followed by their secretion in the culture medium ultimately triggering CD8+ T‐lymphocyte recruitment in vitro. Knock down of MEIS1 expression by siRNA resulted in downregulation of these chemokines. We verified that MEIS1 binds to the promoters of chemokine genes, both in vitro and in vivo. We also showed that the expression levels of MEIS1 correlated tightly with the mRNA levels of chemokines CCL4 and CCL18 in early stage ovarian cancer patient samples and served as a positive prognostic marker, as shown by Kaplan‐Meyer survival analysis. In conclusion, we propose that MEIS1 plays a pivotal role in the regulatory circuitry governing T‐cell chemo‐attraction during the early stages of ovarian cancer.